Nonlinear control of wind power plants using double-fed induction generators based on passive Euler-Lagrange and Hamilton systems. - Hoằng, Đặng Danh; Quang, Nguyễn Phùng (Journal of Computer Science and Cybernetics, 2012)
Applying a novel control method which controls Doubly-Fed Induction Generators (DFIG) in wind power systems in order to evaluate an applicability into practice is a highly important signification. In this research, the passivity based principle has been applied to design a controller for DFIG, in which, Euler - Lagrange (EL) based method and Hamiltonian rules are incorporated. The new controller can overcome static error of the current controller without Hamiltonian rules. The system can also offer exellent performances above and below synchronous speeds of the DFIG with this proposed controller.